2010
DOI: 10.1590/s1984-29612010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Theileria equi in horses raised in the Jaboticabal microregion, São Paulo State, Brazil

Abstract: Blood and serum samples from 170 horses raised in the Jaboticabal microregion, São Paulo State, Brazil, were collected and tested by microscopic examination of blood smears, indirect fluorescent antibody test (IFAT) and nested polymerase chain reaction (nPCR) for Theileria equi infections. The association among the test results was verified by the McNemar test. During the examination of thin blood smears, parasites were detected in six (3.52%) horses. Anti-T. equi antibodies were detected in 100% sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Of 170 horses tested, 96.5% were positive and they were all IFAT positive, considering titers equal to or above 1:80, as demonstrated in a previous study (BALDANI et al, 2010). Several studies have shown that the prevalence of equine piroplasmosis in Brazil is of serious concern.…”
Section: Discussionsupporting
confidence: 59%
“…Of 170 horses tested, 96.5% were positive and they were all IFAT positive, considering titers equal to or above 1:80, as demonstrated in a previous study (BALDANI et al, 2010). Several studies have shown that the prevalence of equine piroplasmosis in Brazil is of serious concern.…”
Section: Discussionsupporting
confidence: 59%
“…In this country, the prevalence among horses ranges from 22 to 100% for T. equi (TENTER & FRIEDHOFF, 1986;PFEIFER BARBOSA et al, 1995;RIBEIRO et al, 1999;HEUCHERT et al, 1999;HEIM et al, 2007;GOLYNSKI et al, 2008;KERBER et al, 2009;BALDANI et al, 2010;SALVAGNI et al, 2010;MACHADO et al, 2012), and from 70 to 90% for B. caballi (PFEIFER BARBOSA et al, 1995;HEIM et al, 2007;KERBER et al, 2009;MACHADO et al, 2012), indicating that both parasites are endemic among horses.…”
Section: Introductionmentioning
confidence: 98%
“…In one previous report (BALDANI et al, 2010) the high positivity rate for T. equi was attributed to the management of horses, which appears to be an important factor for the prevalence of T. equi infections. Additionally, climatic factors such as temperature, relative humidity, altitude and high rainfall influence the habitat of the main tick/vector species that parasite horses (GOLYNSKI et al, 2008).…”
mentioning
confidence: 90%
“…Previous studies in southern and central areas of the country have reported occurrences varying from 49.2% to 100% (HEUCHERT et al, 1999;CUNHA et al, 1996;LABRUNA et al, 2001;XUAN et al, 2001;BALDANI et al, 2004BALDANI et al, , 2010HEIM et al, 2007).…”
mentioning
confidence: 93%
See 1 more Smart Citation